Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0318
|View full text |Cite
|
Sign up to set email alerts
|

Biological Models of Associative Learning

Abstract: Over the last 100 years or so, a great deal of progress has been made in delineating the behavioral properties of simple associative learning. In addition, much progress has been made in defining the neural circuitries involved in encoding learning and memory processes in the nervous system and also some of the cellular and molecular mechanisms that underlie the encoding processes. Advances in our understanding of the behavioral and neural bases of simple associative learning are presented in this chapter. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 330 publications
0
7
0
Order By: Relevance
“…Animal studies have shown that the critical CS-US association occurs in the anterior interpositus nucleus ( Yeo et al, 1985; Steinmetz et al, 1992; Lavond, 2002), one of the deep cerebellar nuclei. The cortex of the cerebellum is thought to control the expression of conditioned responses and modulate both their timing and amplitude (Garcia & Mauk, 1998; Steinmetz, 2000; Steinmetz et al, 2002). The anterior lobe, through Purkinje cells projecting to the interpositus, appears to play a critical role in response timing, delaying the onset of conditioned responses until just prior to the US onset (Garcia et al, 1999; Perrett et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that the critical CS-US association occurs in the anterior interpositus nucleus ( Yeo et al, 1985; Steinmetz et al, 1992; Lavond, 2002), one of the deep cerebellar nuclei. The cortex of the cerebellum is thought to control the expression of conditioned responses and modulate both their timing and amplitude (Garcia & Mauk, 1998; Steinmetz, 2000; Steinmetz et al, 2002). The anterior lobe, through Purkinje cells projecting to the interpositus, appears to play a critical role in response timing, delaying the onset of conditioned responses until just prior to the US onset (Garcia et al, 1999; Perrett et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that the critical CS‐US association occurs in the anterior interpositus nucleus (63–65), one of the deep cerebellar nuclei. The cortex of the cerebellum is thought to control the expression of CRs and modulate both their timing and amplitude (54, 66, 67). The anterior lobe of the cerebellum seems to be specifically involved in response timing.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the past century and the beginning of the present one, classical and instrumental conditioning became essential tools for the study of how organisms learn about their environment, as well as to understand some of the neurobiological mechanisms that underlie it. 1 In classical (or Pavlovian) conditioning, animals learn about events that occur in their environment. For example, in Pavlovian fear conditioning, rats might learn that the presentation of an auditory cue (e.g., a tone) predicts the occurrence of an aversive stimulus, such as a mild foot shock.…”
Section: Introductionmentioning
confidence: 99%